Testing of thermoelectric generator modules and development of DC-DC power converter - Lim, Zi Chuan (2017)
In recent years, due to increase in energy costs and the effect of global warning due to waste heat generated by the industries. Many industries are finding ways to fully utilize the heat waste and convert them to useful energy for power generation. This could be done using the waste heat recovery technology using an application called thermoelectric power generator (TEG). However, TEG module has low power conversion efficiency and it looks very unattractive to others. Thus, to increase the efficiency of the TEG module, a low power conversion systems is need to integrate with the TEG module. This project aims to study and verify the efficiency of the TEG module. Using the data collected, it can derive the TEG characteristics curve and compute the efficiency of the TEG module. This study will allow also the student to program the maximum power point tracking (MPPT) algorithm into the C2000 microcontroller and control the optimum power extracted from the TEG module. The results of this experiment and testing are clearly show in the report.